Management of children who come into conflict with the law during pre-trial stage in Malaysia. Do the current practice and procedures accord to international standards? / Fon Thiam Seong - Fon, Thiam Seong (2015)
Malaysia as a State Party to the Convention on the Rights of the Child and other international instruments are bound by the provisions enshrined in those treaties. Despite all this commitments and obligations, children still experience arbitrary arrest, torture and illtreatment while undergoing police investigation. Still too often, they are deprived of proper treatment that should have been given to them under those treaties. Past literature would show that the rights afforded to children in conflict of the law especially during the pre-trial stage are reduced significantly or in other words not given proper consideration by the enforcement authorities in particular the police and the probation officers even though it is clearly worded in the Child Act 200I . However none of the previous research were able to precisely identify what are the reasons for the non-compliance.